Efficacy of periorbital region rejuvenation with a single session of Erbium:YAG 2940nm fractional laser in dual mode - Hitalo Glauco Fernandes Siqueira; Mariana dos Santos Pereira; Patrícia Rezende Teixeira; Paula Regazzi de Gusmão; Verônica Vilas-Bôas Ferrari Jeovani; Alexandre de Almeida Flippo (Sociedade Brasileira de Dermatologia (SBD), 2023)
Background: Wrinkles and flaccidity in the periocular region are frequent complaints.Ablative fractional lasers (AFL) CO2 10600nm and Erbium:YAG 2940nm can induce neocollagenesis and contraction of collagen fibers. Objective: Our study aimed to observe the effectiveness of one session of dual mode Erbium:YAG 2940nm fractional laser to treat sagging, rhytids, and fat bags of the upper and lower eyelids. Methods: Seventeen patients with sagging, rhytids, and fat bags of the upper and lower eyelids underwent one session of Ablative fractional laser (AFL) 2940nm from the Etherea platform in dual mode. Photographic records were taken in the same environment before treatment and one month after the end of the protocol, and five dermatologists and plastic surgeons independent of the study assessed them objectively. Results: The improvements in the evaluation of rhytids, fine lines, and flaccidity were clinically and statistically significant with few adverse events such as edema, erythema, and desquamation. However, eyelid bags did not improve significantly. Conclusion: A single session with the dual mode AFL Erbium:YAG tip 2940 can contribute to a significant improvement in rhytids, fine lines, and flaccidity of the periorbital area.